2017
DOI: 10.7717/peerj.2908
|View full text |Cite
|
Sign up to set email alerts
|

Neck biomechanics indicate that giant Transylvanian azhdarchid pterosaurs were short-necked arch predators

Abstract: Azhdarchid pterosaurs include the largest animals to ever take to the skies with some species exceeding 10 metres in wingspan and 220 kg in mass. Associated skeletons show that azhdarchids were long-necked, long-jawed predators that combined a wing planform suited for soaring with limb adaptations indicative of quadrupedal terrestrial foraging. The postcranial proportions of the group have been regarded as uniform overall, irrespective of their overall size, notwithstanding suggestions that minor variation may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…Recent studies Naish 2008, 2015;Naish and Witton 2017) have suggested that azhdarchids were pterosaurs adapted for increased terrestrial locomotion. They envision azhdarchids as "terrestrial stalkers", using their tall frame and long neck to ambush unsuspecting prey.…”
Section: Locomotionmentioning
confidence: 99%
“…Recent studies Naish 2008, 2015;Naish and Witton 2017) have suggested that azhdarchids were pterosaurs adapted for increased terrestrial locomotion. They envision azhdarchids as "terrestrial stalkers", using their tall frame and long neck to ambush unsuspecting prey.…”
Section: Locomotionmentioning
confidence: 99%
“…Currie and Russell, 1982;Currie and Jacobsen, 1995;Godfrey and Currie, 2005), all remains are here identified as belonging to azhdarchid pterosaurs. Despite varying degrees of completeness, all cervical vertebrae show some or all of the characteristic features of members of the clade: a low centrum, greatly reduced 'bifid' neural spine (that is, one that has separate anterior and posterior components with a space in between), and dorsoventrally flattened zygopophyses, pneumatic foramina lateral to the neural canal, greatly elongated mid cervicals (e.g., Kellner, 2003;Naish and Witton, 2017;Vidovic and Martill, 2017). Wellnhofer (1970) suggested that the cervical vertebrae of azhdarchids elongate during ontogeny (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially the case for issues such as lengthwidth ratios, which are commonly used in azhdarchid descriptions. Azhdarchids are well known for elongate middle cervicals although recently animals with proportionally short and robust vertebrae have been described (Vremir et al, 2015;Naish and Witton, 2017), further complicating the issues of length-width ratios. However, recent papers (Averianov, 2010;Naish and Witton, 2017) have suggested characteristics that can help identify isolated azhdarchid cervicals and are followed here.…”
Section: Introductionmentioning
confidence: 99%
“…; Lockley & Rainforth ; Mazin et al . ), demonstrates that many of these animals were also adept terrestrial locomotors, and that members of some groups may even have foraged and fed extensively on the ground (Witton & Naish , ; Naish & Witton ). Members of Azhdarchoidea in particular (the toothless, Cretaceous clade that includes the typically gigantic, long‐jawed azhdarchids, the short‐faced tapejarids, and the intermediate chaoyangopterids and thalassodromids) appear to be well adapted for terrestrial behaviour; notably the azhdarchids with their long hindlimbs and compact feet (Witton & Naish , ; Witton ).…”
Section: Institutional Abbreviationsmentioning
confidence: 99%